Pengembangan Kapasitas Agribisnis Sapi Potong melalui Bimbingan Teknis Kelembagaan dalam Upaya Inisiasi Terciptanya Sekolah Peternakan Rakyat di Kabupaten Blora - Anna Fariyanti; Muladno Muladno; Dwi Rachmina; Suharno Suharno; Burhanuddin Burhanuddin; Andriyono Kilat Adhi; Dedi Rahmat Setiadi; Anggraini Sukmawati; Afton Atabani; Triana Gita Dewi; Herawati Herawati; Al-May Abbyan Izzy Burhani (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The development of beef cattle is one of the pillars of the people's economy in the Blora Regency. This activity aims to transfer knowledge and technology to develop the capacity of beef cattle farming agribusinesses to manage livestock reproduction and health, feed, breeding, fattening, management, and social, economic, and network development. This activity was carried out through observation, technical guidance (Bimtek), and mentoring. The Bimtek was divided into six themes, and the assistance was carried out for two months. Sixty breeders carried out the activity from two villages, namely Pengkolrejo Village and Palon Village. From the evaluation results, the Bimtek participants absorbed more than 50 percent of the material. It indicated that all participants experienced increased knowledge and skills of livestock management regarding partnerships and collective business, management, social, economic, and network development, animal reproduction and health, forage and concentrate feed banks, breeding and fattening techniques, and waste management.